(3JcfhdhLjG GdEJUGd hGdeYdheGJ (B/s - (3GdeRGgQI, efGd gdGd s ((3YeGf (B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2014)
(3jVe GdEJUGd hGdeYdheGJ JYQjaGJgG hfXQjGJgG, JcfhdhLjG GdEJUGd hGdeYdheGJ aj GdbQf GdYTQjf, JcfhdhLjG GdJdcS hGdJdJjcS hGdajOjhJcS hGdCbQGU GdCSWhGfjI, JcfhdhLjG GdCdjGa GdVhFjI, JcfhdhLjG GdejcQhhja hGdWja GdcgQheZfGWjSj, JWhQGJ JcfhdhLjG GdEJUGd hGdeYdheGJ, JcfhdhLjG GdJdaRjhf GdcGHdj hGdHK GdeHGTQ, JcfhdhLjG GdJUhjQ GdQbej, hSGFd GdEJUGd GdMOjKI, JcfhdhLjG GdUMGaI GdEdcJQhfjI, LQGFe JcfhdhLjG GdEJUGd hGdeYdheGJ, BKGQ JcfhdhLjG GdEJUGd hGdeYdheGJ GdMOjKI(B. s
(3HHdjhZQGajG(B: (3U(B.429-448s
Keywords: (3GdEJUGds; (3GdeYdheGJ(B- (3JcfhdhLjGs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s